THE LITERARY ZOOLOGY PERSPECTIVE OF BUTTAMBAULE IN PAKKOAYANG TRADITIONAL THEATER - Sri Musdikawati; Rabiatul Adawiah; Chudriah Sahabuddin (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
The Literary Zoology Perspective of Buttambaule in Pakkoayang Traditional Theater. Buttambaule is a poem sung in every traditional Mandarese theater stage, namely Pakkoayang stage. This theater tells thxe story of a bird named Buttambaule. The bird eats fish and does not want to release its prey. Pakkoayang stage uses a sarong costume that is shaped like a bird's head and is accompanied by several figures, namely Koayang (Koayang / Buttambaule), fishermen and shooters. The music of its accompaniment is Parrabana (traditional Mandarese tambourine player). Buttambaule verse is a poem sung by the fisherman who represents the feeling of the fish being eaten by the bird and still in the mouth of the Buttambaule bird. The fish asked to be released by Buttambaule by seducing and praising the bird. Although it took a long time, but in the end Buttambaule released the fish. This research researcher uses qualitative descriptive research methods from the perspective of literary zoology. Literary zoology consists of various points of view including: 1) Literary ornithology is a literary zoology perspective that understands animal literature about birds, 2) literary ichthyology is a literary zoology perspective that understands literature about fish, and 3) literary zoohumorology is a literary zoology perspective that understands animal literature in humor.